Angiotensin-converting enzyme inhibitors and cardiovascular outcomes in patients on maintenance hemodialysis - Chang, Tara I. (2011)
BACKGROUND: Persons with end-stage renal disease (ESRD) on hemodialysis carry an exceptionally high burden of cardiovascular disease. Angiotensin-converting enzyme inhibitors (ACEIs) are recommended for patients on dialysis, but there are few data regarding their effectiveness in ESRD. METHODS: We conducted a secondary analysis of results of the HEMO study, a randomized trial of dialysis dose and membrane flux in patients on maintenance hemodialysis. We focused on the nonrandomized exposure of ACEI use, using proportional hazards regression and a propensity score analysis. The primary outcome was all-cause mortality. Secondary outcomes examined in the present analysis were cardiovascular hospitalization, heart failure hospitalization, and the composite outcomes of death or cardiovascular hospitalization and death or heart failure hospitalization. RESULTS: In multivariable-adjusted analyses, there were no significant associations among ACEI use and mortality (hazard ratio 0.97, 95% CI 0.82–1.14), cardiovascular hospitalization, and either composite outcome. Angiotensin-converting enzyme inhibitor use was associated with a higher risk of heart failure hospitalization (hazard ratio 1.41, 95% CI 1.11–1.80). In the propensity score–matched cohort, ACEI use was not significantly associated with any outcomes, including heart failure hospitalization. CONCLUSIONS: In a well-characterized cohort of patients on maintenance hemodialysis, ACEI use was not significantly associated with mortality or cardiovascular morbidity. The higher risk of heart failure hospitalization associated with ACEI use may not only reflect residual confounding but also highlights gaps in evidence when applying treatments proven effective in the general population to patients with ESRD. Our results underscore the need for definitive trials in ESRD to inform the treatment of cardiovascular disease.